Mexico: What is the impact of monetary policy on unemployment rates? - Alejandro Islas C.; Willy Walter Cortez (CEPAL Review, 2012)
In this paper we analyse the effects of a monetary policy shock on Mexican unemployment rates. Unlike previous studies, this one re-estimates unemployment to produce alternative rates comparable to those of the Organization for Economic Cooperation and Development (oecd) member countries. We find that in response to tightening monetary policy, unemployment increases with a characteristic hump-shaped pattern also found in other studies. Our results are robust to different assumptions about the nature of Mexico’s labour market.